A guide to the project management body of knowledge (PMBOK guide) (PMBOK guide., 2017)
PMI's flagship publication has been updated to reflect the latest good practices in project management. New to the Sixth Edition, each knowledge area will contain a section entitled Approaches for Agile, Iterative and Adaptive Environments, describing how these practices integrate in project settings. It will also contain more emphasis on strategic and business knowledge -- including discussion of project management business documents -- and information on the PMI Talent Triangle™ and the essential skills for success in today's market.